Phase diagrams of ionic liquids-based aqueous biphasic systems as a platform for extraction processes - Sintra, Tânia E.; Cruz, Rafaela; Ventura, Sónia P.M.; Coutinho, João A.P. (The Journal of chemical thermodynamics, 2014)
•Novel ABS based in ionic liquids were determined as a platform for distinct extraction processes.•The effect of pH, IL cation core, alkyl side chain length, IL anion nature, and salt nature on the ABS formation was investigated.•The ability to form ABS increases with the pH and alkyl chain length for all systems studied.•The ILs cation core and anion nature effect on the ABS formation is dominated by the IL (hydrophobic/hydrophilic) nature.•The effect of the different salts depends of the ionic liquid nature and salt valency. In the past few years, ionic liquid-based aqueous biphasic systems have become the subject of considerable interest as a promising technique for the extraction and purification of several macro/biomolecules. Aiming at developing guidelines for more benign and efficient extraction processes, phase diagrams for aqueous biphasic systems composed of ionic liquids and inorganic/organic salts are here reported. Several combinations of ionic liquid families (imidazolium, pyridinium, phosphonium, quaternary ammonium and cholinium) and salts [potassium phosphate buffer (KH2PO4/K2HPO4 at pH 7), potassium citrate buffer (C6H5K3O7/C6H8O7 at pH 5, 6, 7 and 8) and potassium carbonate (K2CO3 at pH ∼13)] were evaluated to highlight the influence of the ionic liquid structure (cation core, anion and alkyl chain length), the pH and the salt nature on the formation of aqueous biphasic systems. The binodal curves and respective tie-lines reported for these systems were experimentally determined at (298±1)K. In general, the ability to promote the aqueous biphasic systems formation increases with the pH and alkyl chain length. While the influence of the cation core and anion nature of the ionic liquids on their ability to form aqueous biphasic systems closely correlates with ionic liquids capacity to be hydrated by water, the effect of the different salts depends of the ionic liquid nature and salt valency.